Analisa Strategi Pemasaran dalam Meningkatkan Penjualan Pupuk pada PT Polowijo Gosari Indonesia - Tiara Adinata; Wasti Reviandani (BADAN PENERBIT STIEPARI PRESS, 2025)
This study analyzes the marketing strategies employed by PT Polowijo Gosari Indonesia to increase fertilizer sales in a competitive agricultural market. The research aims to identify effective marketing approaches including segmentation, targeting, positioning, and the marketing mix elements (product, price, place, promotion) that influence sales performance. Using qualitative methods such as direct observation, interviews, and documentation, the study reveals that PT Polowijo Gosari has implemented comprehensive marketing strategies that successfully expand market reach and customer base. The findings indicate that strategic segmentation of distributor and farmer markets, targeted promotions, and positioning the fertilizer products as superior contribute significantly to sales growth. Moreover, the marketing mix is optimized through product quality, competitive pricing, strategic distribution, and active promotional activities including digital media and exhibitions. The implications of this research suggest that continuous refinement of marketing strategies and expansion of distribution networks are vital for sustaining sales increases in the fertilizer industry. This study provides valuable insights for fertilizer companies aiming to enhance their market competitiveness and sales performance.